Potantial clinical application of potassium binders in patients with chronic heart failure in real life clinical practice: results from TREAT HF study. (25th November 2020) - Cavusoglu, Y; Kaya, H; Murat, S; Yilmaz, B
Abstract: Purpose: Hyperkalemia is increasingly prevalent and life-threatening condition in heart failure (HF). In clinical practice, hyperkalemia is also an important barrier to optimal application of RAASi. New potassium binders, sodium zirconium cyclosilicate and patiromer, were developed for the treatment of hyperkalemia. TREAT HF data were analyzed for the evaluation of potential clinical application of potassium binders in real life clinical care in HF patients. Methods: TREAT HF is a network which undertakes multicenter, national, observational studies designed to evaluate HF patients' clinical characteristics and current treatment modalities. 1028 patients with the diagnosis of chronic HF, median age 64 years and median LVEF 30% who had potassium and GFR data were included in this analysis. In this patient population, 847 patients (82.6%) were receiving beta blockers, 739 (71.9%) were receiving ACE inhibitors or ARBs and 518 (50.4%) were receiving MRA. Patients with hyperkalemia (serum potassium ≥5.1 mEq/L) were considered candidate for potassium binders based on the criteria of HARMONIZE study. According to eGFR (mL/min) level, renal dysfunction was subclassified as: stage-1 (eGFR ≥90) (n=211), stage-2 (eGFR 60-<90) (n=398), stage-3 (eGFR 30-<60) (n=306) and stage 4–5 (eGFR <30) (n=113). Results: In study population, median potassium level was 4.5 mEq/L, median creatinin level was 1.1 mg/dL and median eGFR was 65.5 mL/min. Overall, 82.9% of patients had normal serum potassium levels (≥3.5–5 mEq/l) and 14.3% of patients (n=147) were found to have hyperkalemia (≥5.1 mEq/L) and, hypokalemia was found in 2.8% of patients (n=30). Hyperkalemia was present in 10.9% (n=23) of patients with stage-1, 12.6% (n=50) of patients with stage-2, 17.0% (n=52) of patients with stage-3 and 19.5% (n=22) of patients with stage 4–5 renal dysfunction. In patients with eGFR <60 ml/min (n=419), hyperkalemia was much more prevalent than those with eGFR ≥60 ml/min (n=609) (17.6% and 11.9% respectively, p=0.011). In patients with stage 4–5 renal dysfunction who were receiving ACEI/ARB or combination of ACEI/ARB and MRA (RAASi), more patients had hyperkalemia than those not receiving RAASi therapy (23.4%, 20.0% and 12.5%, respectively). Conclusions: This study suggested that in real life clinical practice, 14.3% of HF patients have hyperkalemia and seem to be eligible for the treatment of potassium binders. The risk of hyperkalemia increases with advanced stages of renal dysfunction and the use of RAASi, showing an increased clinical need for potassium binders in HF patients with renal dysfunction and in those receiving RAASi. Funding Acknowledgement: Type of funding source: None